Prevalence and Factors Associated with Early Postpartum Hemorrhage in Mother undergoing Cesarean Section at Thong Song Hospital, Nakhon Si Thammarat: Benjawan Lahukarn - Makaew, Areewan; Lahukarn, Benjawan (Princess of Naradhiwas University Journal, 2024)
This study is a descriptive retrospective study aimed to investigate the prevalence of early postpartum hemorrhage situations and to determine the relationship between demographic, medical factors, and early postpartum hemorrhage in mothers undergoing abdominal caesarean section at Thung Song Hospital, Nakhon Si Thammarat. The sample was 397 mothers who had a caesarean section from 28 weeks of pregnancy onwards. The research instrument consisted of three parts: Part 1 was personal data, Part 2 was medical factors developed from literature reviews, and Part 3 was postpartum hemorrhage in mothers with caesarean section in which IOC all objectives were 1.00. The data was collected from medical records of pregnant women who had undergone caesarean section during 1 January 2021 – 31 December 2023. General data were analyzed by descriptive statistics; frequency, percentage, standard deviation, and logistic regression analysis. The results were as follows: The prevalence of early postpartum hemorrhage situations in mothers undergoing caesarean section was 29.97 %. Factors that were statistically significantly associated with early postpartum hemorrhage include: demographic factors were gestational age greater than 40 weeks (OR=1.888, 95%CI= 1.037-3.438; p = 0.038), and medical factors were blood loss greater than or equal to 1,000 milliliters (OR = 218.52, 95%CI = 92.978-513.587; p= 0.000). The finding of this study, a healthcare professional team can be deployed to plan care and prevention. Enhance the control of early postpartum hemorrhage in mothers undergoing caesarean section.